PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB PADA MATERI PERAWATAN DAN PERBAIKAN JARINGAN NIRKABEL KELAS XI TKJT DI SMK NEGERI 4 SOLOK SELATAN - Sartika, Reni; Samudra, Ami Anggraini; Novita, Rini (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to develop a valid and practical web-based interactive learning media using the ADDIE model. The study was conducted at SMK Negeri 4 Solok Selatan in Wireless Network Maintenance for grade XI TKJ. The main issue identified was low student engagement and difficulty understanding the material. Validation results showed media experts rated it 88.27% as